Multidrug-resistant tuberculosis (TB) resistant to fluoroquinolones and streptomycin but susceptible to second-line injection therapy has a better prognosis than extensively drug-resistant TB - Chan, Edward D; Strand, Matthew J; Iseman, Michael D (Clinical infectious diseases, 2009)
Multidrug-resistant tuberculosis (TB) strains resistant to the fluoroquinolones and streptomycin but susceptible to second-line injection treatment would not be defined as extensively drug-resistant TB. In a cohort of 174 patients with multidrug-resistant TB, we demonstrated that 12 patients with multidrug-resistant TB strains resistant to the fluoroquinolones and streptomycin had significantly better initial and long-term outcomes, compared with 10 patients with extensively drug-resistant TB.